Mutations in L-type amino acid transporter-2 support SLC7A8 as a novel gene involved in age-related hearing loss - Meritxell Espino Guarch (18810097) (2018)
Age-related hearing loss (ARHL) is the most common sensory deficit in the elderly. The disease has a multifactorial etiology with both environmental and genetic factors involved being largely unknown. SLC7A8/SLC3A2 heterodimer is a neutral amino acid exchanger. Here, we demonstrated that SLC7A8 is expressed in the mouse inner ear and that its ablation resulted in ARHL, due to the damage of different cochlear structures. These findings make SLC7A8 transporter a strong candidate for ARHL in humans. Thus, a screening of a cohort of ARHL patients and controls was carried out revealing several variants inSLC7A8, whose role was further investigated by in vitro functional studies. Significant decreases in SLC7A8 transport activity was detected for patient’s variants (p.Val302Ile, p.Arg418His, p.Thr402Met and p.Val460Glu) further supporting a causative role for SLC7A8 in ARHL. Moreover, our preliminary data suggest that a relevant proportion of ARHL cases could be explained by SLC7A8 mutations. Other Information Published in: eLife License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.7554/elife.31511